Jogos Africanos: aprendendo com estudantes de origem africana matriculados na Universidade Federal de São Carlos - Pereira, Alesandro Anselmo (2019)
The formation of Brazilian culture was strongly influenced by the African peoples and one of the contributions of these habits, customs and traditions was the games that these peoples brought to Brazil. Through games human beings have created cultural and social conditions of learning to play. We believe that the importance of African culture is especially evident in the formation of the Brazilian people, especially when we talk about education, inheritance, traditions are the result of the influences of each culture. In this sense, the objective of this work is to identify the games coming from the countries of African students enrolled in the Federal University of São Carlos (UFSCar) and relate them to the African games in the literature. We used qualitative research as a method of work through the interview. The data collection was performed by an instrument called script, which served as a guide. The testimonies collected were recorded, transcribed and analyzed. As a specific objective, this work intends to contribute to processes of significant changes in our Brazilian society, such as recognizing and respecting different cultures, sharing the cultural wealth of Africa and making available the contents of games of African origin so that they can serve as a subsidy for the work of other educators. As a result, it was observed that African games are also part of the games played by people of different age groups in Brazil. It is also noticed that the playful is a theme full of consensus and conflicts in the field of education.